CUSTOMER PREFERENCE TO SYARIAH CARD - Ihdi Aini (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The purpose of this study was to aimed at determining factors that influence customer preferences in using Sharia Card/iB Hasanah Card of BNI Syariah of the City of Padang by analyzing seven variables, namely sharia and attitudes toward fatwas, brands, features and facilities, services, contracts, fees, and fines. This study, using a qualitative approach. Data collection was done employing structured interview technique by using research instruments in the form of questionnaires. The number of samples taken was 50 customers who used Syariah Card/iB Hasanah Card. To analyze data, Factor Analysis was performed in which the collected data were processed using IBM SPSS Statistics 21. The results showed that of the seven variables that were analyzed, there were four (4) factors that formed and influenced the customer preferences in using Sharia Card/iB Hasanah Card of BNI Syariah of the City of Padang, namely, First: Religious and Rational Factors; factors that are formed from variables‘Contract’ and ‘Cost’ with five statement items. Second: Social Factors; factors that are formed from variables ‘Service’ and ‘Fines’ with five statement items. Third, Psychological factors; factors formed from variables‘Sharia’,‘attitudes toward fatwas’, and ‘Brand’ with four statement items. Fourth: Product Factors; factors that are formed from variables ‘Feature’ and ‘Facility’ with two statement items.